Influencer Marketing Strategies and Brand Image in Boosting Consumer Purchase Intent: The Role of Customer Support Intervention - Sandra, Jana; Indrayanti, Sri; Suryana, Ade (Jurnal Informatika Ekonomi Bisnis, 2024)
This research explores the intricate relationships among influencer marketing strategies, brand image, customer support, and consumer purchase intent within the operational framework of PT. Len Industri (Persero) - Jakarta Office. Through path analysis, the study discerns direct and indirect effects, revealing significant findings. Marketing Strategies exhibit a notable direct impact on both Customer Support and Consumer Purchase Intent, underscoring the centrality of effective marketing initiatives in shaping customer interactions and purchase decisions. Conversely, Brand Image reveals a non-significant direct effect on Customer Support but demonstrates a marginally significant impact on Consumer Purchase Intent, indicating a nuanced relationship that warrants further investigation. The indirect effects analysis highlights the substantial influence of Marketing Strategies on Consumer Purchase Intent mediated by Customer Support. These findings underscore the importance of a holistic approach, integrating marketing strategies, brand image cultivation, and effective customer support to enhance overall consumer experiences and drive purchase intent in a competitive market landscape.